Atomic and molecular gas in the environs of the ring nebula RCW 78 - Cappa, Cristina Elisabeth (2005)
We present a study of the neutral atomic and molecular gas associated with the ring nebula RCW 78 around the WR star HD 117688 (WR 55) based on H I 21cm line data and CO(1--0) observations obtained with SEST. The analysis of the neutral atomic gas distribution reveals a H I shell, which is interpreted as the neutral gas counterpart of the optical ring nebula RCW 78, while the CO observations show the presence of molecular material interacting with the nebula. The surface of the detected molecular cloud has probably been photodissociated and ionized by the UV photons from the WR star.